Using the shifting standards model of stereotype‐based judgments to examine the impact of race on compensation decisions. Issue 3 (18th November 2020) - Weeks, Matthew; Weeks, Kelly P.; Watkins, Emily C.
Abstract: The Shifting Standards Model (SSM) of stereotypic judgments is presented as a model of implicit bias that produces a psychological mechanism contributing to continued racial wage disparities. The SSM is used to explain race‐based differences in subjective evaluations of compensation decisions. We report three experimental studies in which research participants made compensation decisions for either a White or Black employee. Across three studies, participants judged a Black employee's raise as subjectively better than a comparably described White employee's raise. Participants who work in Human Resources fields (Study 3) and those with experience making compensation decisions (Study 2) were as likely as other participants to show evidence of the shifting standards effect. The findings are discussed in the context of individual implicit biases contributing to continued wage disparities and potential organizational practices to ameliorate these influences.